Myopia in Asian Subjects with Primary Angle Closure - Yong, Kai-Ling; Gong, Tianxia; Nongpiur, Monisha E.; How, Alicia C.; Lee, Hwee Kuan; Cheng, Li; Perera, Shamira A.; Aung, Tin (Ophthalmology (Rochester, Minn.), 2014)
To evaluate the occurrence of myopia in Asian subjects with angle closure and to assess the ocular biometric parameters in these subjects. Cross-sectional study. We prospectively recruited 427 angle-closure subjects (143 primary angle-closure suspects, 75 patients with primary angle closure, 165 patients with primary angle-closure glaucoma, and 44 patients with acute primary angle closure) from a Singapore hospital. Refractive status was derived from the spherical equivalent of autorefraction. A-scan biometry (Nidek Echoscan Ultrasound US-800; Nidek Co., Tokyo, Japan) was performed to obtain anterior chamber depth (ACD), axial length (AL), lens thickness, and vitreous cavity length (VL). Anterior segment optical coherence tomography was performed to measure lens vault. Refractive status was categorized as myopia (≤−0.50 diopter [D]), emmetropia (−0.50 to +0.50 D), and hyperopia (≥+0.50 D). The mean age ± standard deviation of study subjects was 65.6±7.6 years, with most being Chinese (n = 394; 92.3%) and women (n = 275; 64.4%). Overall, myopia was present in 94 subjects (22%), hyperopia was present in 222 subjects (52%), and emmetropia was present in 111 subjects (26%). Of the 94 myopic angle-closure patients, 28 (29.8%) were categorized as having moderate myopia (≤−2.0 to −5.0D) and 11 (11.7%) were categorized as having high myopia (≤−5.00 D). Although myopic angle-closure subjects had longer ALs (P<0.001) and VLs (P = 0.001) than their emmetropic and hyperopic counterparts, there were no significant differences in ACD (P = 0.77), lens thickness (P = 0.44), or lens vault (P = 0.053). Almost one quarter of angle-closure patients were myopic. Myopic angle-closure subjects had longer VLs and ALs, but there was no difference in ACD. With the increasing rate of myopia in many East Asian populations, there may be many subjects with axial myopia but shallow ACD and angle closure. The implication is that ophthalmologists should not assume that glaucoma patients who are myopic have open angles.